Alterations in lipid profile in gestational diabetes mellitus (GDM) and type 2 DM women during pregnancy - K., Vani (International Journal of Medical Research and Review, 2015)
Objective: To study the effect of gestational diabetes mellitus (GDM) and type 2 diabetes mellitus (DM) on indices of lipid profile in maternal blood samples and compare them with normal pregnancies. Methodology: Blood samples were collected from 45 normal pregnant women and 30 women with GDM and 15 women with type 2 DM during pregnancy. Serum lipids which include Total Cholesterol, Triglycerides, Very Low Density Lipoprotein, Low Density Lipoproteinand High Density Lipoprotein were estimated using semi-automated clinical chemistry analyzer. Results: The results of the lipid profile showed elevated levels of Total Cholesterol, Triglycerides, Very Low Density Lipoprotein and Low Density Lipoprotein in women with GDM and pregnant type 2 DM women compared to controls. On the other hand,the High Density Lipoprotein levels were significantly elevated in controls. Conclusion: In Gestational Diabetes Mellitus and type 2 DM during pregnancy, the lipid profile alters in such manner that could be atherogenic and possibly harmful to the fetus.